2019
DOI: 10.3389/fmolb.2019.00021
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Chemistry in Liquid Phase Separated Compartments

Abstract: Biochemical processes inside the cell take place in a complex environment that is highly crowded, heterogeneous, and replete with interfaces. The recently recognized importance of biomolecular condensates in cellular organization has added new elements of complexity to our understanding of chemistry in the cell. Many of these condensates are formed by liquid-liquid phase separation (LLPS) and behave like liquid droplets. Such droplet organelles can be reproduced and studied in vitro by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
183
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(184 citation statements)
references
References 89 publications
1
183
0
Order By: Relevance
“…[21,52,53] Membrane-free droplets can hence be described as "open" reactors, capable of rapid molecular exchange with their environment without the need for active transport machineries (Figure 2A). [55] Low-molecular-weight solutes do not usually exhibit high levels of partitioning in neutral polymer ATPSs. [54] Althought he driving forces behind selectives olute partitioning remainp oorly understood, factors such as the charge, hydrophobicity,s ize or shape of biomolecular solutes, together with the chemical natureo ft he LLPS components,h ave been invoked to account for the solutes' uptake or exclusionb y aqueous droplets.…”
Section: Bridging the Gap With Living Cells:i Ntracellular Biomoleculmentioning
confidence: 99%
See 3 more Smart Citations
“…[21,52,53] Membrane-free droplets can hence be described as "open" reactors, capable of rapid molecular exchange with their environment without the need for active transport machineries (Figure 2A). [55] Low-molecular-weight solutes do not usually exhibit high levels of partitioning in neutral polymer ATPSs. [54] Althought he driving forces behind selectives olute partitioning remainp oorly understood, factors such as the charge, hydrophobicity,s ize or shape of biomolecular solutes, together with the chemical natureo ft he LLPS components,h ave been invoked to account for the solutes' uptake or exclusionb y aqueous droplets.…”
Section: Bridging the Gap With Living Cells:i Ntracellular Biomoleculmentioning
confidence: 99%
“…Experimental and theoretical studies in ATPSs showed only poor reactionr ate enhancement for a pair of enzymesi nvolved in ac oncertedc ascade reaction, due to the low degree of partitioning of enzymes in the droplets. [55,82] Elucidation and explanation of the connections between differential partitioning, upconcentration, crowding, chemical composition, protein conformation etc. [81] By compartmentalising dextranase in ac oacervate subcompartment within the dextran droplet, substrate inhibition was mitigated and dextranase-mediated interfacial dextran hydrolysis was restored.…”
Section: Bridging the Gap With Living Cells:i Ntracellular Biomoleculmentioning
confidence: 99%
See 2 more Smart Citations
“…Several methodologies have been developed to sequester specific biochemical processes to defined locations and to emulate functions of natural cellular organelles (3). Examples include the use of coacervates (4)(5)(6), hydrogels (7)(8)(9), as well as protein (10,11) and polymer (12) assemblies to spatially organize biomolecules. In eukaryotic cells, compartmentalization is primarily achieved by lipid bilayer membranes that demarcate the boundary to the outside world and enclose classical organelles.…”
Section: Introductionmentioning
confidence: 99%